Steep terrain forest operations – challenges, technology development, current implementation, and future opportunities. Issue 3 (2nd September 2019) - Cavalli, Raffaele; Amishev, Dzhamal
ABSTRACT: While modern fully mechanized ground-based systems are a default option for safe and productive harvesting, they have always been limited by terrain factors such as slope, soil strength, and roughness. There is a limit with regard to the physical feasibility of operating machines on steep slopes because both the weight and also the force from the momentum created during traction loss can affect stability. A huge interest to improve traction of harvesting machines when operating on steep slopes is arising. One way to improve traction and stability on steep slopes is through assisting harvesting machines by winch and cable to anchor locations such as tree stumps or stationary equipment. This technology offers potential for improving the safety, productivity, and efficiency of a harvesting operation, as well as for improving machine mobility and reducing soil disturbance through the reduction of slip. With the exponential development of such technology, an integrated approach must be developed for conducting productive and injury-free mechanical harvesting operations on steep slopes that draws on the skills and accountabilities of the working team. Beyond a certain physical threshold, the only feasible and achievable solution providing some "intelligent behavior" to machines and systems would be the role of mechatronics application. One of the most relevant points could be the possibility to introduce the concept of "teleoperation" using unmanned ground vehicles. Combining teleoperation with winch-assist technology would provide a platform for extending the range of ground-based equipment to previously infeasible terrain conditions.